Syekh Imam Mahyudin al-Khalidi dan Perannya dalam Penyebaran Tarekat Naqsyabandiyah di Nagari Koto Baru (1978-2023) - Azizul Rahman; Siti Fatimah (Jurnal Kronologi, 2026)
This study examines the urole of a local ulama in the development of the Naqshbandiyah order in Nagari Koto Baru, Sngai Tarab District, Tanah Datar Regency, with particular attention to Syekh Imam Mahyudin al-Khalidi. Previous studies have generally examined the order at the regional level or focused on prominent figures, leaving the role of nagari-level religious leaders in the contemporary period underexplored. This study traces Syekh Imam Mahyudin’s life and scholarly genealogy and analyzes his role in developing the order between 1978 and 2023. The historical method was employed through four stages: heuristics, source criticism, interpretation, and historiography. Data were collected from interviews with six informants, family documents, photographs, the Surau Talang endowment document, and relevant literature. The findings indicate that Syekh Imam Mahyudin assumed the leadership of Surau Talang in 1978 after receiving a mandate from his teacher, Syekh Abdurrahman Malin Batuah, whose scholarly lineage was connected to Syekh Abdurrahman al-Khalidi, known as Syekh Kumango. He maintained the order’s principal religious activities while developing adaptive forms of community engagement through Silat Kumango and the Al-Badriah shalawat group. These approaches enabled Surau Talang to engage congregants from diverse social backgrounds and supported the continuity of the Naqshbandiyah order and its religious activities until his death in 2023.